Growth of African Catfish (Clarias gariepinus) Cultured Using the Biofloc System at Different Stocking Densities - Aisyah, Nur; Scabra, Andre Rachmat; Mulyani, Laily Fitriani (Journal of Fish Health, 2025)
The cultivation of African catfish (Clarias gariepinus) using a biofloc system is an aquaculture technology that integrates waste management and the production of natural feed in situ, thereby enhancing productivity efficiently. This research aimed to evaluate the effect of EM4 probiotic application in a biofloc system on the growth and survival rate of catfish under different stocking densities. The experiment was conducted using a Completely Randomized Design (CRD) with four stocking density treatments: P1 (30 fish/30 L), P2 (40 fish/30 L), P3 (50 fish/30 L), and P4 (60 fish/30 L), each with three replications. Observed parameters included absolute weight and length growth, floc content, hematocrit, hemoglobin, erythrocytes, leukocytes, differential leukocytes and water quality parameters. The treatment P4 showed the most notable effects, with a final absolute weight gain of 11.66 grams and an absolute length increase of 8.11 cm. Furthermore, the probiotic addition had a significant impact on erythrocyte levels and differential leukocyte counts. In contrast, the use of probiotics in the biofloc system did not result in significant differences in hematocrit levels, total leukocyte counts, or biofloc volume.